Improving The Quality of Education Through Healthy Optimization and Literacy Association - Dewi Lestari Pardede; Immanuel Padang; Gloria Sirait; Irving Josafat Alexander (PT. TAROMBO RESEARCH DEVELOPMENT, 2026)
The quality of education is not solely determined by academic aspects, but is also influenced by the social and cultural environment of students' literacy. Low interest in reading and suboptimal positive social interactions among adolescents pose challenges that can hinder the development of critical thinking skills, character, and academic achievement. This community service activity aims to increase students' understanding of the importance of healthy social interactions and literacy as supporting factors for quality education. The activity was carried out at SMP Negeri 31 Medan through socialization, interactive discussions, educational games, and group mentoring for eighth-grade students. A qualitative approach was used, using simple observation and interview techniques to identify students literacy levels prior to the activity. The results showed that students reading interest was still relatively low, especially in grades VIII-2 and VIII-3. Most students also found reading activities uninteresting and did not yet understand literacy concepts comprehensively. After the outreach activities, students demonstrated an increased understanding of the importance of literacy and positive social interactions in supporting academic success. This activity proves that the integration of literacy education and the creation of a healthy social environment can be an effective strategy in supporting the improvement of the quality of education at the secondary school level.